The Implementation of Educational Facilities and Infrastructure Inventory at SMP Negeri 12 Palembang - Lestari, Ayu; Choirun Niswah; Lia Efriliyanti (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to analyze the implementation of educational facilities and infrastructure inventory management at SMP Negeri 12 Palembang, as well as to identify the challenges and solutions in its implementation. This research employed a descriptive design with a qualitative approach. The informants in this study included the Vice Principal for Facilities and Infrastructure, the Principal, and the Head of Administration. Data collection techniques were conducted through interviews, observations, and documentation, while data analysis followed the stages of data reduction, data display, verification, and conclusion drawing. The validity of the data was ensured through source and technique triangulation. The results indicate that the implementation of facilities and infrastructure inventory management at SMP Negeri 12 Palembang has been carried out fairly well. This is reflected in the presence of motivation, guidance, coordination, and communication in the inventory process. However, several challenges were identified, including limited human resources responsible for inventory management, the large number of items, limited storage space, and the accumulation of unusable items that have not yet been officially removed from inventory records. The proposed solutions include strengthening coordination among stakeholders, utilizing digital recording systems to facilitate inventory data management, and enhancing supervision by school leaders to ensure a more organized and systematic implementation of inventory management.